1995
DOI: 10.1002/dir.4000090406
|View full text |Cite
|
Sign up to set email alerts
|

The use of black models in specialty catalogs

Abstract: Although there are a wealth of studies which examine the use of minority models (particularly African American models) in advertising, we found no research that addresses the use of black models in direct marketing vehicles, that is, specialty catalogs. W e conducted a content analysis of 1 1 1 clothing and gift catalogs to determine benchmarks on the use of black models in catalogs. Generally, we found that black models in specialty catalogs tend to be used in similar proportions to magazine advertisements an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…No significant differences in the status images of black and white models were found. Likewise, Wilson and Biswas (1995) found that black models are not limited to advertising lower priced goods in direct marketing catalogues. Changes in the composition of racially mixed advertising have also been observed.…”
Section: Black People In Advertising: the American Perspectivementioning
confidence: 97%
“…No significant differences in the status images of black and white models were found. Likewise, Wilson and Biswas (1995) found that black models are not limited to advertising lower priced goods in direct marketing catalogues. Changes in the composition of racially mixed advertising have also been observed.…”
Section: Black People In Advertising: the American Perspectivementioning
confidence: 97%
“…Furthermore, this study provides insight on the print advertising landscape as it relates to services marketers. Unfortunately, several prior research studies have found that minority groups are either underrepresented (Kassarjian, 1969; Wilson and Biswas, 1995; Wilkes and Valencia, 1989; Zinkhan et al , 1990), or portrayed in a stereotypical fashion (Taylor and Stern, 1997; Colfax and Sternberg, 1972; Bang and Reece, 2003; Taylor et al , 1995) across different types of advertising media. These studies provide vital information on the diversity of images being viewed by consumers.…”
Section: Introductionmentioning
confidence: 99%